Visualization of Record Swapping - Jiří Novák; Jaroslav Sixta (Austrian Journal of Statistics, 2024)
Record Swapping is a statistical disclosure control technique widely used to secure the confidentiality of microdata obtained in surveys and censuses. It is one of the methods recommended by the Centre of Excellence on Statistical Disclosure Control of the European Union for the protection of data from Census 2021. This method is based on the swapping of risk records between geographical areas. The analysis of perturbed microdata is usually done purely on numerical results, and only simplified schemes are used for general illustration. We wanted a comprehensive visualization, and therefore, we have prepared a~ visualization of record swapping based on Choropleth maps and Commuting Flow maps, also known as Origin-Destination maps. Choropleth maps use differing colours within predefined geographic areas to represent aggregated statistical data. Origin-Destination maps are widely used for visualization and a description of people commuting to work, but they can also be used to describe other indicators. We utilize these methods to visualize the swapping of records for individual statistical units (persons). This approach is demonstrated using microdata from the Population Census 2011 from the Czech Republic and synthetic Austrian EU-SILC data. The proposed visualization allows statistical offices and agencies to effectively evaluate the swapping process and the distribution of the records across geographical areas.